On the relationships between information theories and their computing implications - Harviainen, Tuomas (Informaatiotutkimus, 2020)
A Review of Antonio Badia’s The Information Manifold: Why Computers Can’t Solve Algorithmic Bias and Fake News (MIT Press, 2019). 352 pages.